MAKNA KARIKATUR INTERPRETATIF NABI MUHAMMAD PADA COVER MAJALAH CHARLIE HEBDO (Analisis Semiotika Roland Barthes Cover Depan Majalah Perancis Charlie Hebdo Edisi 19 September 2012) - Rizki Amalia Yanuartha; Sih Natalia Sukmi (Cakrawala Jurnal Penelitian Sosial, 2013)
Starting from the emergence of protest actions against the publication of drawing image of the Prophet Mohammed caricatures interpretive on magazine cover of the French edition of 19 September 2012. The image is the main image of the magazine cover issue is consider as mocking and have insulted the Prophet Muhammad. As we know that the Prophet Muhammad is the Apostle gives the teachings of Islam and described in the Hadits that all living things must not be portrayed visualization including all the prophets.  The main image of the magazine cover portrayed two characters with each identity attached to them. Main Image then became a controversy with the pros and cons in response to magazine cover picture Charlie Hebo 19 September 2012 Edition.   The aim of this research is to know the connotative meaning of Prophet Mohammed caricature on Charlie Hebdo magazine cover, therefore using semiotics Roland Barthes as a tool for analyzing a magazine cover is the best way from point of view of researcher. Conclusion of this research is the main image of Charlie Hebdo magazine cover issued September 19, 2012 was a cartoon of the Prophet Mohammed caricature rather than opinion. On the connotation of retrieved the meaning that this opinion cartoon series about the second film The Intouchables titled Intouchables 2 with people from the Arabs and Europeans.             Keywords: magazine cover, caricatures, controversies, semiotics Roland Barthes.